2017
DOI: 10.1038/s41598-017-04845-9
|View full text |Cite
|
Sign up to set email alerts
|

Clues on the origin of post-2000 earthquakes at Campi Flegrei caldera (Italy)

Abstract: The inter-arrival times of the post 2000 seismicity at Campi Flegrei caldera are statistically distributed into different populations. The low inter-arrival times population represents swarm events, while the high inter-arrival times population marks background seismicity. Here, we show that the background seismicity is increasing at the same rate of (1) the ground uplift and (2) the concentration of the fumarolic gas specie more sensitive to temperature. The seismic temporal increase is strongly correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 80 publications
2
73
1
Order By: Relevance
“…Chiodini, Selva, et al () have showed that Pisciarelli fumarolic tremor, recorded 8 m away from the fumarole‐mud pool alignment (CPIS station), has the following characteristics: (1) it has a spectral peak in a narrow frequency band around 10 Hz; (2) its polarization is almost vertical; and (3) the frequency content and the polarization parameters (azimuth, inclination, and rectilinearity) have not significantly changed from January 2010 to May 2017. Furthermore, even if the Campi Flegrei seismic network is very dense, the fumarolic tremor with characteristic frequency around 10 Hz is not detectable by seismic stations located 200 or 300 m away from the fumarole.…”
Section: Data Analysis: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chiodini, Selva, et al () have showed that Pisciarelli fumarolic tremor, recorded 8 m away from the fumarole‐mud pool alignment (CPIS station), has the following characteristics: (1) it has a spectral peak in a narrow frequency band around 10 Hz; (2) its polarization is almost vertical; and (3) the frequency content and the polarization parameters (azimuth, inclination, and rectilinearity) have not significantly changed from January 2010 to May 2017. Furthermore, even if the Campi Flegrei seismic network is very dense, the fumarolic tremor with characteristic frequency around 10 Hz is not detectable by seismic stations located 200 or 300 m away from the fumarole.…”
Section: Data Analysis: Methods and Resultsmentioning
confidence: 99%
“…We divided the signal into eight intervals of 30 min, and we calculated the RSAM as the average of the absolute values of the counts of each interval. We chose the minimum of the 8 values to select the least noisy window, obtaining a daily RSAM value [see Chiodini, Selva, et al, , for details]. Figure shows the time series of the CPIS RSAM updated to 23 April 2019.…”
Section: Data Analysis: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The length scales for most of these processes are dependent on details of the magmatic‐hydrothermal system and are hence difficult to ascertain. With regard to timescales, observations from volcanic systems with high‐frequency geophysical and geochemical monitoring suggest that the typical timescale for magmatic fluid injection is of order 1 month to 10 years (e.g., Campi Flegrei, Chiodini et al, ; Cascade volcanoes, Crankshaw et al, ; Long Valley Caldera, Peiffer et al, ; Shelly et al, ).…”
Section: Transient Permeabilitymentioning
confidence: 99%
“…The Campi Flegrei caldera (CFc), next to Naples in southern Italy, has been the world's most restless, non-erupting caldera for the last 69 years, characterized by episodes of significant ground uplift, enhanced hydrothermal activity, and seismicity. In addition to these short-term episodes (e.g., 1950-1952, 1969-1972, and 1982De Natale et al, 2006;Del Gaudio et al, 2010;Troiano et al, 2011;Chiodini et al, 2015Chiodini et al, , 2017Kilburn et al, 2017;Moretti et al, 2017Moretti et al, , 2018, ground subsidence and uplift of several meters has been documented since at least Roman times (e.g., Bellucci et al, 2006;Di Vito et al, 2016). Moreover, as a result of resurgence over the last ca.…”
Section: Introductionmentioning
confidence: 99%